2008
DOI: 10.1021/la702473y
|View full text |Cite
|
Sign up to set email alerts
|

Drop Retention Force as a Function of Drop Size

Abstract: The force, f, required to slide a drop past a surface is often considered in the literature as linear with the drop width, w, so that f/w = const. Furthermore, according to the Dussan equation for the case that the advancing and receding contact angles are constant with drop size, one can further simplify the above proportionality to f/V(1/3) = const where V is the drop volume. We show, however, that experimentally f/V(1/3) is usually a decaying function of V (rather than constant). The retention force increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 28 publications
3
56
0
Order By: Relevance
“…The trend shown in Fig. 3a is valid for a variety of drop-solid systems studied so far 4,12,17,[21][22][23] .…”
Section: Resultssupporting
confidence: 58%
“…The trend shown in Fig. 3a is valid for a variety of drop-solid systems studied so far 4,12,17,[21][22][23] .…”
Section: Resultssupporting
confidence: 58%
“…Recent work has shown that the retention force may be a function of time so the ability to photograph the droplet in a quick and consistent manner is important [17]. According to Yadav et al [18], the error in the measured advancing and receding contact angles due to this droplet resting time would be less than ±0.4 • and 0.6 • , respectively, which is within the experimental uncertainty of this work. The camera was mounted opposite to a light source on an arm that could be rotated around a fixed plate containing the test surface and droplet.…”
Section: Introductionsupporting
confidence: 62%
“…[29]. A shadowgraph system was used to illuminate, from behind, sessile droplets resting on a substrate mounted on a rotational stage.…”
Section: Methodsmentioning
confidence: 99%